Synthesis and Characterization of Terephthalic Acid MOF as a Catalyst for Biodiesel Production from Waste Cooking Oil - Rista Haryana; Nurlisa Hidayati; Hasanudin Hasanudin (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Utilization of waste cooking oil as a raw material for biodiesel production is an effective solution to reduce environmental pollution and produce renewable energy. The high free fatty acid content in waste cooking oil is a major problem in the industry, so it requires an effective catalyst in the biodiesel production process. Zn terephthalate MOF has a large surface area, porous structure, and good thermal stability, making it very effective as a heterogeneous catalyst for the biodiesel esterification process. This study aims to synthesize and characterize Zn terephthalate MOF using a hydrothermal method with a Teflon autoclave, and evaluate its effectiveness as a catalyst. The analysis was carried out by testing the acidity of the Zn terephthalate MOF catalyst characterized by XRD, TGA, PSA, and the ability to convert waste cooking oil into biodiesel. The results showed that the obtained MOF-5 had an acidity of 4.33 mmol/g, the XRD results showed a 2 theta angle and the catalyst intensity was the same as JCPDS no. 96-432-6738. TGA results showed that the Zn terephthalate catalyst had thermal stability up to 300OC, and PSA results showed particles distributed at 8428.62 nm. This proves that the Zn terephthalate MOF catalyst can reduce the FFA value of waste cooking oil and convert it into biodiesel with a conversion rate of 94.18%, and the catalyst can be reused up to five times with relatively stable performance